Study of Scientific Reasoning and Concept Mastery of Students Through Guided Inquiry Learning Model Assisted by Formative Assessment - Saiya, Selvina Visbad; Kusairi, Sentot; Sunaryono, Sunaryono (Sekolah Pascasarjana Universitas Negeri Malang (UM), 2023)
This study endeavors to assess the impact of guided inquiry learning, complemented by formative assessment, on students’ scientific reasoning (SR) and concept mastery (CM). The research involved 20 students from class XI A at SMA Muhammadiyah 02 Sumberpucung, utilizing questions adapted from the modified Lawson classroom test of scientific reasoning (MLCTSR) to measure SR, and the force concept inventory (FCI) to gauge CM. The instructional focus was Newton’s law of motion. Both qualitative and quantitative analyses were employed for data interpretation. The findings revealed a substantial influence of the guided inquiry learning model on SR, with a d-effect size value of 3.829. Similarly, students’ CM exhibited a noteworthy impact, evidenced by a d-effect size value of 3.099. These values signify that both SR and CM fall within the category of greater than the standard effect size. The outcomes imply a significant enhancement in students' proficiency in both SR and CM as a result of the guided inquiry learning approach.DOI: 10.17977/jps.v11i22023p072